The Influence Of Education And Leadership Levels On The Performance Of Village Officials In The Karangnunggal Sub-District - Fuji Umahatul Mahira; Kusuma Agdhi Rahwana; Ai Kusmiati Asyiah (Journal of Management, Economic, and Accounting, 2023)
The purpose of this study is to determine the influence of education and leadership levels on the performance of village officials in the Karangnunggal District Area. The research method used is a causal associative method of quantitative approach to 50 respondents who are village officials, namely Cidadap Village, Kujang Village, Sarimukti Village, Cikapinis Village. The types of data used are primary and secondary. The technical data analysis used is multiple linear regression analysis. The results of this test prove that the level of education and leadership has a significant effect both partially and simultaneously on the performance of village officials in the Karangnunggal District Area.